Diffusion tensor imaging in abdominal organs. (11th November 2015) - Lanzman, Rotem Shlomo; Wittsack, Hans‐Jörg
Abstract : Initially, diffusion tensor imaging (DTI) was mainly applied in studies of the human brain to analyse white matter tracts. As DTI is outstanding for the analysis of tissue´s microstructure, the interest in DTI for the assessment of abdominal tissues has increased continuously in recent years. Tissue characteristics of abdominal organs differ substantially from those of the human brain. Further peculiarities such as respiratory motion and heterogenic tissue composition lead to difficult conditions that have to be overcome in DTI measurements. Thus MR measurement parameters have to be adapted for DTI in abdominal organs. This review article provides information on the technical background of DTI with a focus on abdominal imaging, as well as an overview of clinical studies and application of DTI in different abdominal regions. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Diffusion tensor imaging of abdominal organs adds additional diagnostic information about the microstructure of human tissues. Besides the technical requirements for DTI in abdominal organs, recent studies of major organs such as kidney, liver, prostate and pelvic floor are presented and discussed.